Rancang Bangun Sistem Informasi Kepegawaian Pada PT Tawan Cemerlang Abadi - Tanner, Stefanus; Elizabeth, Triana (Universitas Multi Data Palembang, 2024)
PT Tawan Cemerlang Abadi is a company engaged in the distribution of snacks. This company has several problems related to the existing human resources system, such as suboptimal employee data search, unsynchronized employee data, lengthy leave request processes, the absence of records related to human resources reports, inflexible attendance system, and the possibility of missing payroll slips. PT Tawan Cemerlang Abadi requires a human resources information system that can provide convenience for every employee in the company to carry out various human resources processes. This human resources system is built based on a website and utilizes the Rational Unified Process (RUP) methodology, which consists of four phases: Inception, Elaboration, Construction, and Transition. The design of this system uses PHP as the programming language and MySQL as its database. The development of this human resources information system aims to address the current issues faced by PT Tawan Cemerlang Abadi.